Gambaran Karakteristik dan Pengetahuan Ibu Menyusui tentang Puting Susu Lecet di Klinik Romana Tanjung Anom Kecamatan Pancur Batu Tahun 2022 - Trismilan Margaret Hondro; Desriati Sinaga; Ermawaty Arisandi (Jurnal Maternitas Kebidanan, 2022)
Background: Nipple blisters are nipple skin that is injured due to irritation, cracks or cracks. Knowledge greatly influences mothers in making decisions because the better the mother's knowledge, the lower the incidence of sore nipples. This is because through high knowledge the mother will know more information about the correct way of breastfeeding, so that the mother does not experience sore nipples when breastfeeding so that the mother can give breast milk to her baby because she does not feel pain anymore when breastfeeding. Destination: for know the Description of the Characteristics and Knowledge of Breastfeeding Mothers About Sore Nipples at Romana Tanjung Anom Clinic, Pancur Batu District 2022. Method: character descriptive. The sample in this study were all mothers who gave birth and breastfeeding mothers from the age of 0-30 days as many as 32 respondents at the Romana Tanjung Anom Clinic, Pancur Batu District 2022. The sampling technique is total sampling with instrument study use processed questionnaire in SPSS form. Results: Research results obtained that which knowledge enough as many as 16 respondents (50%), knowledgeable good as many as 13 respondents (40.6%) and knowledgeable not enough as many as 3 respondents (9.4%). Conclusion: Enough knowledge caused by lack of information mother breastfeeding about sore nipples. Suggestion: it is advised to health workers to optimize not using milk bottles for babies because it makes babies confused about nipples and provide health education to breastfeeding mothers about nipple care so they don't get chafed.